Development of an Ethernet-Based Heuristic Time-Sensitive Networking Scheduling Algorithm for Real-Time in-Vehicle Data Transmission - Hyeong-jun Kim (Electronics, 2021)
The rapid development and adaptation of advanced driver assistance systems (ADAS) and autonomous driving increases the burden of in-vehicle networks. In-vehicle networks are now required to provide a fast data rate and bounded delay for real-time operation, while conventional protocols such as controller area networks, local interconnected networks, and FlexRay begin to show limitations. Ethernet-based time-sensitive network (TSN) technology has been proposed as an alternative. TSN is a set of Ethernet standards being developed by the IEEE TSN task group, which aims to satisfy requirements such as real-time operation, stability, and low and bounded latency, and it can be used in automotive, industrial, and aerospace applications. This study introduces several standards for Ethernet traffic scheduling based on TSN technology and proposes a heuristic-based scheduling algorithm for Ethernet scheduling. In addition, three network configurations are simulated using OMNeT++ to show the applicability. The heuristic TSN scheduling algorithm is a straightforward and systematic procedure for practical network designers.